Aesthetic Multiple-Toe Reconstruction With Combined Iliac Bone Graft and Wraparound Free Anterolateral Thigh Flap—A Case Report and Literature Review. (March 2017) - Kwon, Soo-Ha; Lao, William; Yen, Cheng-I; Lin, Yu-Te; Wu, Katie Pei-Hsuan; Chang, Tommy Nai-Jen
Abstract : Abstract: Compared with upper extremity injuries, toe amputations and their replantations are rare because of the difficulty of their relatively thinner soft tissue envelope. Consequently, fewer reconstructive options are available for toes and they are rarely reported in the literature. In this study, we reported a case of right third to fifth toe amputations and their subsequent reconstruction with iliac bone grafts and a free anterolateral thigh flap. After serial debulking and division procedures, 3 toes were divided successfully. Ten months after the initial operation, the patient regained pain-free functional ambulation despite some bone resorption noted on follow-up radiographs. The patient showed high satisfaction on her new toes in terms of aesthetical and functional outcomes. She was able to stand for over 30 minutes without pain. At the 2-year follow-up, the Foot Function Index was 18.3%. Although toe reconstruction is frequently considered unnecessary because of its relative high demand of surgical techniques and little gain on gait; nonetheless, in selected cases, toe reconstruction may still be beneficial if the metatarsophalangeal joints were intact and there is a strong individual desire for aesthetical restoration. Abstract : Supplemental digital content is available in the text.